Holographic correlation functions from wedge - Tengzhou Lai; Ya-Wen Sun; Jia Tian (Journal of High Energy Physics)
Abstract In this work, we propose a novel holographic method for computing correlation functions of operators in conformal field theories. This method refines previous approaches and is specifically aimed at being applied to heavy operators. For operators that correspond to particles in the bulk, we show that the correlation functions can be derived from the on-shell actions of excised geometries for heavy operators, using numerical and perturbative calculations. These excised geometries are constructed from various background solutions such as Poincaré AdS3, global AdS3, and BTZ by cutting out a wedge bounded by two intersecting End-of-the-world branes and the AdS boundary. The wedge itself can be interpreted as a dual to a BCFT with cusps in the AdS/BCFT framework. Additionally, we calculate the correlation functions for heavy operators directly by constructing backreacted bulk geometries for particle excitations through coordinate transformations from a conical solution. We find that the on-shell actions of these backreacted solutions accurately reproduce correlation functions, although they differ from those computed in Fefferman-Graham(FG) gauge. This discrepancy, previously noted and explained in our earlier work, is reinforced by additional examples presented here.